Synthesis of spherical structured catalysts by dip-coating: Application to n-butane dehydrogenation - Ballarini, Adriana Daniela (2017)
This work analyzes the deposition conditions of thin layers of γ-Al2O3 by dip-coating on a spherical substrate of α-Al2O3 spheres. Results showed that under controlled deposition conditions, a structured support of α-Al2O3 spheres coated by a uniform γ-Al2O3 layer (thickness≈15μm) of good adherence can be attained. Optimal preparation conditions for the coating, that involved pretreatment of the substrate, gel formation, deposition conditions, and thermal treatments, were obtained. Pt catalysts supported on this structured material can be used as promising dehydrogenation systems. In this sense, a monometallic structured catalyst showed both good metallic dispersion and catalytic performance in n-butane dehydrogenation reaction compared to another conventional catalytic system.